FASAD CANDI BOROBUDUR SEBAGAI IDE PERANCANGAN DESAIN TIPOGRAFI UNTUK ASET VISUAL BRANDING KABUPATEN MAGELANG - Hafiyan, R. Moch. Rizal; Pratama, Novan Edo (Universitas Mercu Buana, 2022)
Visual branding can be an attraction for tourists to visit in certain areas. Various forms of visual branding in each city and district have begun to be developed with an effort to increase the interest of both local and international tourists to come. Visual branding can also be a visual design asset that can be used to package tourism products using the right visual design assets. One of the things that supports visual branding in an area is the type of typography or font design. Each city or district should have its own typographic design that characterizes the area. Magelang Regency with a fairly well-known tourist spot, namely the Borobudur temple, is a quite interesting tourist destination. However, until now, the design of visual branding, especially typography which is a characteristic of tourism in the Magelang Regency area, has not been fully facilitated, especially since Borobudur is included in the 5 super priority destinations according to the Indonesian Ministry of Tourism and Creative Economy. For this reason, by taking ideas from the facade of the Borobudur temple as an idea in designing typography for Magelang Regency's visual branding assets as an effort to support super priority destination areas. In this design using the design design method with the stages of exploring the source of ideas, experimentation, and formation or embodiment. This design is expected to provide useful visual branding assets for the development of Tourism in Magelang Regency.